Optimal Experience and Optimal Identity: A Multinational Study of the Associations Between Flow and Social Identity - Mao, Yanhui; Roberts, Scott; Pagliaro, Stefano; Csikszentmihalyi, Mihaly; Bonaiuto, Marino (Frontiers in Psychology, 2016)
Eudaimonistic identity theory posits a link between activity and identity, where a self-defining activity promotes the strength of a person’s identity. An activity engaged in with high enjoyment, full involvement, and high concentration can facilitate the subjective experience of flow. In the present paper, we hypothesised in accordance with the theory of psychological selection that beyond the promotion of individual development and complexity at the personal level, the relationship between flow and identity at the social level is also positive through participation in self-defining activities. Three different samples (i.e., American, Chinese, and Spanish) filled in measures for flow and social identity, with reference to four previously self-reported activities, characterized by four different combinations of skills (low versus high) and challenges (low versus high). Findings indicated that flow was positively associated with social identity across each of the above samples, regardless of participants’ gender and age. The results have implications for increasing social identity via participation in self-defining group activities that could facilitate flow.